Paulo Freire's Critical Pedagogy and His Contributions to Current Costa Rican Higher Education - Espinoza Arroyo, Manuel Gerardo (2021)
Costa Rican higher education at present faces a series of challenges that attempt against its general autonomy and institutionality. Therefore, in this context, this paper has the main objective to analyze Paulo Freire´s pedagogical proposal and his educational contributions to Costa Rican higher education nowadays. Consequently, this essay seeks to deepen three aspects, which the Brazilian pedagogue contributes to public Costa Rican universities: dialogue, dialectical thought, and transformation. In addition, every single aspect will be explained from the Freirean viewpoint in addition to thinking about the enforcement of it in the Costa Rican context.